Novel Side Information Generation Algorithm of Multiview Distributed Video Coding for Multimedia Sensor Networks - Fu Xiao; Jinkai Liu; Jian Guo; Linfeng Liu (International Journal of Distributed Sensor Networks)
The traditional multiview distributed video coding scheme using regional unified coding may lead to distortion problem of decoding estimation of the intense motion region. This paper presents a novel multiview distributed video coding algorithm. In the main perspective, gaining the intense motion regions of Wyner-Ziv frame according to the criteria of ROI, the algorithm extracts their DCT low-frequency coefficients for the entropy coding, in order to generate the best temporal side information. For the nonintense motion regions, the algorithm utilizes motion compensation interpolation (MCI) to generate side information. Finally, side information based on fusion of temporal and spatial side information will be gained. Experimental results show that our proposed algorithm can gain more accurate motion estimation in the intense motion region. Quality of decoded image is improved with the same transmit rate; thus, energy consumption of sensor nodes will be decreased ultimately.